DEVELOPING EFFECTIVE TIME MANAGEMENT SKILLS AMONG UNDERGRADUATE STUDENTS - Affandi, Akhmad; Fadlih, Andi Muhammad; Abdullah, Ahmad Rizal; Nurwahida, Nurwahida; Ahmad, Ardiansyah (Jurnal Gembira: Pengabdian Kepada Masyarakat, 2025)
This report presents the design, implementation, and evaluation of a Time Management Training program tailored for undergraduate students. The training aimed to equip students with practical strategies to effectively manage their academic and personal responsibilities. Utilizing a combination of interactive activities, self-assessment tools, and real-life case studies, the program provided participants with opportunities to identify personal time management challenges, develop actionable skills, and engage in reflective goal setting. Results indicate significant improvements in students’ self-awareness, problem-solving abilities, and motivation to adopt effective time management habits. Group discussions and peer learning fostered a supportive community, while experiential exercises bridged the gap between theory and practice. The findings highlight the importance of integrating time management training into student development initiatives, as such interventions can enhance academic performance, reduce stress, and prepare students for future success. Recommendations for sustaining these benefits include ongoing support and the incorporation of time management modules into broader university programs.